EVALUATING THE ANTI-BACTERIAL ACTIVITY OF MYCELIUM EXTRACT FROM DIFFERENT WOOD-DECAY-FUNGUS SPECIES COLLECTED IN SOUTHERN VIETNAM - Hoa, Pham Thi; Vu, Ngo Nguyen; Phuong Linh, Tran Thi (Vietnam Journal of Biotechnology, 2018)
The antibacterial activity of twelve different wood-decay fungal isolated in Southern Vietnam was investigated to find out the new potential antibiotics produced by macro fungi. The antibacterial activity of the collected fungal isolates was tested by three screening methods against seven different strains of bacteria: Bacillus subtilis, Enterococcus faecalis, Staphylococcus aureus, Escherichia coli, Vibrio parahaemolyticus, Vibrio cholerae, and Salmonella typhi. The screening test were performed at first with mycelium grew on surface of agar medium similar to a disc diffusion test, next by an extracellular metabolite test by flood-plate method, and finally with an intracellular metabolite test using grounded mycelium fluid. To determine the activity of metabolites produced in the mycelium, the fungal isolates were grown on culture substrates to promote mycelium formation. Antibacterial activity of the selected fungi was confirmed by disc diffusion method using crude extract of the mycelium harvested from the substrate cultures. Four fungal species identified with strong antibacterial compounds produced by their mycelium including Pycnoporus sanguineus, Flavodon flavus, Fomitopsis ostreiformis and Meripilus giganteus. Crude extract of Pycnoporus sanguineus showed the strongest antibacterial activity, with 7/7 bacterial strains inhibited. Fomitopsis ostreiformis antibacterial activity was recognized with the ability to inhibit 6/7 bacterial strains. Flavodon flavus and Meripilus giganteus showed weaker activity than other two species, with only 4/7 strains inhibited. The fungal isolates identified with antibacterial activity discovered in this study can be potential candidates for the new source of antibiotic to fight against new generations of antibiotic resistance bacteria in the future.